10.47313 Pembentukan TNI Angkatan Siber dalam Perspektif Teori Geometripolitisasi (Mazhab Indonesia) dan Sekuritisasi (Mazhab Kopenhagen) terhadap Ruang Siber di Indonesia untuk Menghadapi Perang Siber Global - Adi Rio Arianto; Gesti Anggraini (Universitas Nasional, 2025)
Law Number 3 of 2025 concerning Amendments to Law Number 34 of 2004 on the Indonesian National Armed Forces (TNI Law) focuses on adjusting the duties, functions, and structure of the TNI in response to the dynamics of modern defense threats (cyber and hybrid). This article examines the urgency of establishing a cyber army, namely the Indonesian National Armed Forces Cyber Force, from the perspective of the theory of Geometripolitization and the securitization of cyberspace. This study employs a qualitative approach using a literature review method and conducts a comparative analysis of the theory of Geometripolitics/Geometripolitization through the lens of the Indonesian School of World Relations, specifically “Manunggalisme,” and the Securitization approach of the Copenhagen School. The findings indicate that the transformation of global cyber warfare in the 21st century has created a new battlefield in cyberspace; Indonesia’s cyber securitization is carried out by framing the complexity of Global Cyber Warfare as a national threat; Indonesia’s cyber geometripolitization is conducted by linking balance, power, and security to realize the role of a Cyber Army, which has the potential to become the TNI Cyber Force; and Indonesia must respond to 21st century Global Cyber Warfare by advocating for the establishment of the TNI Cyber Force under the legal framework of Law No. 3 of 2025 concerning Amendments to Law Number 34 of 2004 on the Indonesian National Armed Forces. Abstrak Undang-Undang Nomor 3 Tahun 2025 tentang Perubahan Perubahan Atas Undang-Undang Nomor 34 Tahun 2004 tentang Tentara Nasional Indonesia (UU TNI) berfokus pada penyesuaian tugas, fungsi, dan struktur TNI menghadapi dinamika ancaman pertahanan modern (siber dan hibrida). Artikel ini mengkaji urgensi pembentukan tentara siber, yaitu TNI Angkatan Siber dalam perspektif teori Geometripolitisasi dan sekuritisasi ruang siber. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka dan melakukan analisis komparatif teori Geometripolitika/Geometripolitisasi pendekatan Mazhab Indonesia (Indonesian School of World Relations) “Manunggalisme” dan Sekuritisasi pendekatan Mazhab Kopenhagen (Copenhagen School). Hasil kajian menunjukkan bahwa transformasi perang siber global Abad 21 menciptakan medan tempur baru di ruang siber; Sekuritisasi siber Indonesia dilakukan dengan cara membingkai kompleksitas Perang Siber Global sebagai salah satu ancaman nasional; Geometripolitisasi siber Indonesia dilakukan dengan cara menghubungkan keseimbangan, kekuatan, dan keamanan untuk meraih peran Tentara Siber yang berpotensi menjadi TNI Angkatan Siber; dan Indonesia harus merespon Perang Siber Global abad ke-21 dengan cara mewacanakan pembentukan TNI Angkatan Siber di bawah payung hukum UU No. 3 Tahun 2025 tentang Perubahan Atas Undang-Undang Nomor 34 Tahun 2004 tentang Tentara Nasional Indonesia.